Возрастные и сезонные изменения некоторых физиологических показателей у ласки и горностая - Туманов, И.Л.; Левин, В.Г. (Вестник зоологии, 1974)
In the process of individual development of animals (within the range of a species) a clear dependence is observed between the intensit,7 of energetic metabolism and cardiac activity on the one hand, and body weight and age of animals, on the other. The amount of consumed oxygen (per weight unit) as well as respiration and pulse frequency diminish in young animals with age. In adult animals the intensity of metabolic processes is not constant during a year but changes by seasons, reaching its maximum in summer and spring.